New Firm Survival: Industry versus Firm Effects - David B. Audretsch; Patrick Houweling; A. Roy Thurik (Tinbergen Institute, 1997)
Recent studies show that the likelihood of survival differs significantly across firms. Both firm and industry characteristics are hypothesized to account for this heterogenity. Using a longitudinal database of manufacturing firms we investigate whether firm or industry characteristics dominate. Our evidence suggests that both firm- and industry-specific characteristics shape new-firm survival during the first years subsequent to entry. However, in the longer run, most of the industry factors have little influence on the likelihood of survival, but firm-specific characteristics still exert a considerable influence in shaping firm survival rates.
Keywords: 330; Unternehmensgründung; Unternehmenserfolg; Niederlande